Feed Efficiency and Blood Hematology of Broiler Chicks Given a Diet Supplemented with Yeast Culture - Al-Mansour, S.; Al-Khalf, A.; Al-Homidan, I.; Fathi , M.M. (International Journal of Poultry Science, 2011)
A study was conducted to evaluate the effect of supplemental yeast culture (Diamond V XP Yeast Culture; YC) in broiler diets on growth performance and hematological parameters. One-day-old Ross 308 broiler chicks (n = 240) were randomly assigned to 1 of 4 dietary treatments based on corn and soybean meal containing 0, 1, 1.25 (recommended level) and 1.5 g/kg of YC in the diet over 42 days. Each treatment group had 60 birds divided into 4 replicates. All birds were kept under the same managerial, environmental and hygienic conditions except for different dietary levels of yeast. Feed consumption, weight gain and feed conversion were measured on 3 week-interval basis. At 42 days of age three birds were chosen randomly from each replicate for determination of hematological parameters. The results of this study indicate that dietary supplemental YC at 1.25 g/kg (recommended level of the manufactory) improved growth performance. However, this improvement was not statistically differed. The chicks fed supplemented diets with YC in the rate of 1.5 g/kg had significantly (p